Current global status of male reproductive health - De Jonge, Christopher J. (2024)
The widespread interest in male reproductive health (MRH), fueled by emerging evidence, such as the global decline in sperm counts, has intensified concerns about the status of MRH. Consequently, there is a pressing requirement for a strategic, systematic approach to identifying critical questions, collecting pertinent information, and utilizing these data to develop evidence-based strategies. The methods for addressing these questions and the pathways toward their answers will inevitably vary based on the variations in cultural, geopolitical, and health-related contexts. To address these issues, a conjoint ESHRE and Male Reproductive Health Initiative (MRHI) Campus workshop was convened.